2019
DOI: 10.17547/kjsr.2019.27.4.396
|View full text |Cite
|
Sign up to set email alerts
|

Negative Urgency Mediates the Relation between Negative Emotion and Smartphone Addiction

Abstract: Background: Negative urgency is a tendency to engage in rash behaviors when experiencing negative emotions such as depression, anxiety, and stress, and is known to predict addictive behaviors. This study aimed to investigate the effect of negative urgency on smartphone addiction as one of behavioral addictions. Methods: Self-report questionnaires were administered to 350 college (graduate) students to assess the level of depression, anxiety, stress, negative urgency, and smartphone addiction. Results: Regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
1
4
0
2
Order By: Relevance
“…Negative urgency has been shown to mediate the relationship between negative emotion and smartphone addiction (57). Moreover, smartphone addiction may serve as a mediator between loneliness and sleep quality (30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative urgency has been shown to mediate the relationship between negative emotion and smartphone addiction (57). Moreover, smartphone addiction may serve as a mediator between loneliness and sleep quality (30).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have also shown that smartphone addiction is often associated with social media addiction because social media use is primarily engaged in via smartphones ( 55 , 56 ). Negative urgency has been shown to mediate the relationship between negative emotion and smartphone addiction ( 57 ). Moreover, smartphone addiction may serve as a mediator between loneliness and sleep quality ( 30 ).…”
Section: Introductionmentioning
confidence: 99%
“…De hecho, se considera un endofenotipo transdiagnóstico de los trastornos adictivos (Um, Whitt, Revilla, Hunton y Cyders, 2019), el abuso de drogas, el juego problemático, las conductas sexuales de riesgo y los atracones (Cyders, Coskunpinar y VanderVeen, 2016;Fischer, Wonderlich, Breithaypt, Byrne y Engel, 2018). En la misma línea, la urgencia negativa se ha relacionado con la adicción a los teléfonos inteligentes, como mediador decisivo en la relación entre el trastorno por estrés postraumático, la depresión, la ansiedad y el estrés con PSU (Contractor et al, 2017;Lee y Lee, 2019). Como el desarrollo de las adicciones tiende a responder a la necesidad de escapar de las emociones negativas, podría ser que el uso del teléfono inteligente cumpla la función de evitar el enfrentamiento a las emociones negativas presentes en la realidad (Li et al, 2021).…”
Section: Discussionunclassified
“…Negative emotions are unpleasant or unhappy feelings which often include depression, anxiety, loneliness, anger and stress. 22 , 23 Moreover, negative emotions arise as a result of the interaction of both traumatic events that occur in the external environment and related subjective experiences. Negative emotions such as anxiety, anger, helplessness and panic were commonly experienced by the public in response to the sudden outbreak of the Covid-19 infection.…”
Section: Literature Reviewmentioning
confidence: 99%